Hawkeye: Kate Bishop. Vol. 2 , Masks - Thompson, Kelly, 1976- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2017)
"Hawkeye finally gets a lead on the top-secret case that brought her out to Los Angeles in the fi rst place -and it might be more than she bargained for... In order to solve this mystery, Kate will have to take a good hard look and who she is and where she came from. But is she really ready to face the ghosts of her past" -- Amazon.